FRIENDS AND BROTHERS - King-Smith, Dick; Walters, Jessica (United Kingdom : Sweet Cherry Publishing Limited, 2021)
It's not easy having a younger brother, William finds. Especially one like Charlie who shows off, asks a million questions and will say "absolutely" all the time. But when Charlie is in trouble, William is the first to come to the rescue. After all, they are friends and brothers.
Keywords: Children's stories, English; Sibling rivalry -- Juvenile fiction; Brothers and sisters -- Juvenile fiction